2016
DOI: 10.1556/030.63.2016.023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hemin, CO2, and pH on the branching of Candida albicans filamentous forms

Abstract: Morphological transitions of wild-type and oxidative stress-tolerant Candida albicans strains were followed in the RPMI-FBS culture medium at pH values and CO 2 levels characteristic for the anatomical niches inhabited by this opportunistic human pathogen fungus, including the oral cavity as well as the intestinal and vaginal lumens. Selected cultures were also supplemented with hemin modeling bleedings. Germination as well as elongation and branching of hyphae were monitored in the cultures using time-lapse v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…In in vitro cultures of C. albicans , these acidic pH values are usually permissive of yeast, not hyphal growth. At the relatively high CO 2 concentration and metabolite-rich environment (as in the vagina), the fungus can also grow under filamentous forms but these are dominantly pseudo-hyphae (Jakab et al, 2016). Acidic pH causes cell wall remodeling with un-masking of beta-glucan (Sherrington et al, 2017), a fact that has been previously demonstrated in VVC patients (Pericolini et al, 2018; Roselletti et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In in vitro cultures of C. albicans , these acidic pH values are usually permissive of yeast, not hyphal growth. At the relatively high CO 2 concentration and metabolite-rich environment (as in the vagina), the fungus can also grow under filamentous forms but these are dominantly pseudo-hyphae (Jakab et al, 2016). Acidic pH causes cell wall remodeling with un-masking of beta-glucan (Sherrington et al, 2017), a fact that has been previously demonstrated in VVC patients (Pericolini et al, 2018; Roselletti et al, 2019).…”
Section: Discussionmentioning
confidence: 99%